KOMPARATIF KISAH NABI ISA DALAM AL-QUR'AN DAN INJIL - Hafiz Rahimi, Zukhruf; Arif Fadhilah, Muhammad (Al-I'jaz: Jurnal Kewahyuan Islam, 2021)
AbstractThis study analyzes the narrative of the story of Prophet Jesus in the Qur'an and the Gospel to reveal similarities and differences from theological, historical, and philological perspectives. This study uses a descriptive-analytical and comparative approach, with primary sources in the form of verses from the Qur'an (Surah Maryam, Surah Ali 'Imran, and others) and the Gospels (Matthew, Luke, John). Secondary sources include classical and modern Qur'anic interpretations and Gospel commentaries. The main findings show that both books share universal themes such as the miraculous birth and the eschatological role of Prophet Jesus, but have fundamental differences in the concept of divinity and prophecy. The Qur'an emphasizes Tawhid and the position of Jesus as a prophet, while the Gospel describes Jesus as the Son of God within the framework of the doctrine of the Trinity. Philological analysis of key terms such as "Isa" and "Jesus Christ" also reveals the influence of the linguistic and cultural contexts of each book. This study provides new insights to support inclusive interfaith dialogue, and suggests further research to improve understanding of the narrative of the scriptures in a global context.Keywords: Prophet Jesus; Al-Qur'an; Gospel; comparative narrative; interfaith dialogue.